Sulfur Resistance of Pt-W Catalysts - Carolina P. Betti; Juan M. Badano; Ivana L. Rivas; Vanina A. Mazzieri; M. Juliana Maccarrone; Fernando Coloma-Pascual; Carlos R. Vera; Mónica E. Quiroga (Journal of Chemistry)
The sulfur resistance of low-loaded monometallic Pt catalysts and bimetallic Pt-W catalysts during the partial selective hydrogenation of styrene, a model compound of Pygas streams, was studied. The effect of metal impregnation sequence on the activity and selectivity was also evaluated. Catalysts were characterized by ICP, TPR, XRD, and XPS techniques. Catalytic tests with sulfur-free and sulfur-doped feeds were performed. All catalysts showed high selectivities (>98%) to ethylbenzene. Activity differences between the catalysts were mainly attributed to electronic effects due to the presence of different electron-rich species of Pt0 and electron-deficient species of Ptδ+. Pt0 promotes the cleavage of H2 while Ptδ+ the adsorption of styrene. The catalyst successively impregnated with W and Pt (WPt/Al) was more active and sulfur resistant than the catalyst prepared with an inverse impregnation order (PtW/Al). The higher poison resistance of WPt/Al was attributed to both steric and electronic effects.